Subacute Bacterial Endocarditis with Leptotrichia goodfellowii in a Patient with a Valvular Allograft: A Case Report and Review of the Literature - Wilfredo R. Matias; Daniel L. Bourque; Tomoko Niwano; Andrew B. Onderdonk; Joel T. Katz (Case Reports in Infectious Diseases)
Leptotrichia species are normal constituents of the oral cavity and the genitourinary tract microbiota that are known to provoke disease in immunocompromised patients and rarely in immunocompetent individuals. Following the description of Leptotrichia goodfellowii sp. nov., two cases of endocarditis by this species have been reported. Here, we report a case of Leptotrichia goodfellowii endocarditis in an immunocompetent patient with a valvular allograft. The isolation and identification of Leptotrichia can be challenging, and it is likely that infection with this pathogen is significantly underdiagnosed. A definitive identification, as in this case, most often requires 16S rRNA gene sequencing, highlighting the increasingly important role of this diagnostic modality among immunocompetent patients with undetermined anaerobic bacteremia.